Screening potential inhibitors of lactate dehydrogenase from Plasmodium knowlesi via virtual screening approaches - Ahmad Fuad, Fazia Adyani; Ogu Salim, Nurhainis (Malaysian Society of Parasitology and Tropical Medicine, 2017)
Lactate dehydrogenase from Plasmodium knowlesi (Pk-LDH) has been suggested as a potential therapeutic target for the development of drugs against malaria disease. This paper reported the screening of compounds which have potentials to be developed as drugs specific for malaria caused by P. knowlesi via in silico screening. Due to the unavailability of Pk-LDH crystal structure, a protein model was built based on the crystal structure of the closest similar protein, lactate dehydrogenase from Plasmodium falciparum (Pf-LDH) with 91% sequence identity between the two enzymes. The model was developed using MODELLER program and verified in Structural Analysis and Verification Server. Primary and secondary structure features were determined and based on Globplot, two disordered regions were predicted at amino acid numbers 85-95 and 269-281. Meanwhile, results of PPCpred server predicted that Pk-LDH is crystallisable with predicted crystallisation propensity of 0.766. Verification of the model was performed with the ERRAT quality factor of 92.2% while Verify 3D gave the percentage of 85.76%. Ligand-based drug design was performed using Ultra-Fast Shape Recognition with Atom Types (USFRAT) with scores for compounds most resemble oxamate ranged from 0.832-0.914. Meanwhile, the results from structure-based screening using Autodock4 and Cygwin gave minimum binding energies ranged from -3.59 to -0.07. Taken together, this study has successfully generated a verified model structure of Pk-LDH and yielded a list of compounds that have potentials to be developed as antimalarial drugs.